2022
DOI: 10.1186/s12889-022-14578-8
|View full text |Cite
|
Sign up to set email alerts
|

Dementia is (not) a natural part of ageing: a cross-sectional study on dementia knowledge and misconceptions in Swiss and Italian young adults, adults, and older adults

Abstract: Background Increasing public awareness and understanding of dementia is the second key action area of the 2017 WHO Global action plan on a public health response to dementia. To achieve this aim, the first indispensable step is to understand the average level of dementia knowledge and to identify areas of low dementia knowledge. We aimed to quantify dementia knowledge in the general population, and to explore the extent to which it differs by age, sex, education, and indirect experience with de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…Additionally, we found that people with higher education, particularly those who attained a postgraduate degree (β=2.42, p=0.012), had a higher level of knowledge of dementia. This observation aligns with previous studies investigating the public knowledge of dementia [6,8,[52][53][54]. Socioeconomic factors strongly predict health results, as shown many times in the scientific literature [55].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, we found that people with higher education, particularly those who attained a postgraduate degree (β=2.42, p=0.012), had a higher level of knowledge of dementia. This observation aligns with previous studies investigating the public knowledge of dementia [6,8,[52][53][54]. Socioeconomic factors strongly predict health results, as shown many times in the scientific literature [55].…”
Section: Discussionsupporting
confidence: 91%
“…DKAS score at the 60th percentile (i.e., a score of 30) was chosen to correspond to sufficient knowledge about dementia. The literature has utilized similar procedures to identify cutoff scores [8,26]. Table 2 shows the mean and SD for each DKAS item.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, interest in dementia care was signi cant predictors of dementia knowledge scores. This result was similar to the ndings of Dong et al(4) and Paci co et al (33). Although nursing students are lack of knowledge and have little clinical practice, fortunately, most of them are interested in dementia care and would like to have more opportunities for dementia education as well as training in professional skills.…”
Section: Differences In Dementia Knowledge According To Demographic C...supporting
confidence: 89%
“…This rapidly expanding eld recognizes brain health as more than just the absence of disease, and emphasizes the need to enhance protective factors across the life course (11,12). A handful of studies to date have investigated knowledge and attitudes towards brain health in individuals as young as 18 (10,(13)(14)(15)(16)(17)(18). However, no brain health studies have been designed to speci cally target young adults, nor has any study been implemented with their unique interests and needs in mind.…”
Section: Introductionmentioning
confidence: 99%